Research and Thinking on the Aggregation and Dispatching Control Framework of Virtual Power Plant's Large Scale Flexible Resources - Tianqi SONG; Zhipeng LV; Zhenhao SONG; Yunting MA; Zhihui ZHANG; Shan ZHOU; Hao LI (Zhongguo dianli)
In the background of the "cloud-edge collaboration + Internet of Things", in order to provide a comprehensive resource structure basis and a systematic regulation framework for dynamic performance quantitative analysis of virtual power plant (VPP), this paper conducts a comprehensive survey and systematic analysis of the existing and potential VPP's large-scale flexible resources, and makes a study on the grid access system and grid controllability of the resources. On this basis, a comprehensive systematic aggregation and regulation framework of VPP large-scale flexible resources is constructed, which integrates three paths and adapts to multiple scenarios and conditions. Based on the proposed framework, the reference principles are given for the research on the "Cloud-edge collaboration + Internet of Things" architecture of the VPP dynamic performance quantitative analysis and evaluation system, and the research directions of relevant VPP mechanisms are also discussed.